2019
DOI: 10.1177/0272684x19858015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Concept of Food Insecurity and Family Hunger in Senegal, West Africa

Abstract: Using a previously validated instrument, surveys were conducted by researchers in a Senegalese village to elicit data on childhood food insecurity and health outcomes. Fifty-four participants were interviewed and completed the Community Childhood Hunger Identification Project (CCHIP) survey. More than half of the adults experienced hypertension or diabetes and also reported childhood food insecurity. The role of food coping strategies and social support were identified as factors that minimized the burden of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This concept of interembodiment allows us to see how health and illness are, moreover, an intergenerational experience (Walker et al. 2020). Maïmouna and Diarra's narrative illustrates the way these shared experiences comprise intergenerational health, as a mother, her daughter, and a lost infant—three generations of women—are affected by diabetes.…”
Section: Maïmouna Diaw and Diarra Fall's Storymentioning
confidence: 99%
“…This concept of interembodiment allows us to see how health and illness are, moreover, an intergenerational experience (Walker et al. 2020). Maïmouna and Diarra's narrative illustrates the way these shared experiences comprise intergenerational health, as a mother, her daughter, and a lost infant—three generations of women—are affected by diabetes.…”
Section: Maïmouna Diaw and Diarra Fall's Storymentioning
confidence: 99%
“…With a population of over 308 million people, more than 40 million people are undernourished and suffer from severe malnutrition and hunger (Food and Agriculture Organization of the United Nations, 2017; Grote, 2018; Food Security Information Network, 2018). Recent studies (Benzekri et al, 2021; FSIN, 2020; Walker et al, 2020; Food Security Information Network, 2018), which have indicated that 13 West African countries are experiencing food insecurity that requires immediate remedies. This worrying situation is predicted to worsen, as experts have indicated that nearly 13 million people could face hunger in Nigeria next year, as against 9.2 million at present, and 2.7 million in Burkina Faso, from two million facing hunger currently (Gobal Network Against Food Crisis, ).…”
Section: Introductionmentioning
confidence: 99%
“…The 2020 analysis of the situation in the region (Bhargava, 2018; Rehman et al, 2021; Steinwand & Ronald, 2020; Thornton et al, 2018; Tomiyama et al, 2020) demonstrated that Nigeria has 9.2 million people in food crises, followed by Burkina Faso with 3.3 million (Benzekri et al, 2021; Davies et al, 2020; FSIN, 2020; Houessou et al, 2020; Walker et al, 2020). Ten other countries, including Cameroon, Chad, Guinea, Guinea Bissau, Liberia, Mali, Mauritania, Niger, Sierra Leone, and Senegal, have significant portions of their populations experiencing acute food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Non-Communicable Diseases, in particular hypertension and diabetes, are increasingly common among people in middle and older age in Senegal (Macia et al, 2016 ; Ndiaye et al, 2016 ; Vialard et al, 2017 ; Walker et al, 2019 ). In the low-income, food-insecure households in which I conducted my research, diagnoses of hypertension and diabetes were almost ubiquitous and the majority of older people I spoke to told me that they were taking steps to eat a healthy diet and improve their health.…”
Section: Introductionmentioning
confidence: 99%